Pemanfaatan Metode Triple Exponential Smoothing Dalam Peramalan Penjualan Pada PT.Dinamika Daya Segara Malang - Tistiawan, Tutur Ade; Andini, Titania Dwi (Jurnal Ilmiah Teknologi Informasi Asia, 2019)
PT Dinamika Daya Segara Malang is one of a company that engages in marketing sector. Selling out the products will be the main purpose of the company. Because each district company would got both monthly and semester target from the main office. Besides that, in this office does not have supporting forecasting system sales in the next period. To determine the right forecasting method, writer needs to understand the data pattern used in the experiment. As for one of the selling out product at PT. Dinamika Daya Segara Malang is Cream detergent Ekonomi / Wings Biru 900K soap in the January 2013 – April 2016 period will be the object for the example calculation in this journal. From the data, it gained unstable pattern. So, forecasting process in this report using Triple Exponential Smoothing method. As for calculation, forecasting process used constant alpha 0.1 – 0.9. Calculating an error for each alpha is intended to get minimum error, so that it will be better forecasting. By the calculation forecasting calculations result is gets the smallest mean absolute percentage error (MAPE) is 10.04% uses constant alpha 0.1 and the outcome in May 2016 is 96.22 boxes. So by using forecasting system in this company might be help to get forecasting in the next period sales and determining selling out strategy in the next period.